Technical efficiency of small-scale industry: application of stochastic production frontier model - Nikaido, Yuko (2004)
In the 1950s, the focus of policy-making for SSI was on protection. With the onset of liberalisation in 1991. SSI was recognised as a growth engine of the economy and the government urged to make the attendant policy changes. Section II of the paper measures the technical efficiency of SSI by using a stochastic production frontier model. Section III analyses the impact of firm size and individual agglomeration on the measured technical efficiency in order to arrive at policy implications for SSI sector. - Reproduced.
Keywords: India - Industries, Small scale; Small scale industry